An Extension of Chebyshev's Maximum Principle to Several Variables (Communications in Mathematical Research, 2021)
In this article, we generalize Chebyshev's maximum principle to severalvariables. Some analogous maximum formulae for the special integration functionalare given. A sufficient condition of the existence of Chebyshev's maximum principleis also obtained.
Keywords: cubature formula; orthogonal polynomial; Chebyshev's maximum principle; nonstandard Gaussian quadrature.